Performance Comparison of Fault-Tolerant Three-Phase Induction Motor Drives Considering Current and Voltage Limits - Tousizadeh, Mahdi; Che, Hang Seng; Selvaraj, Jeyraj; Rahim, Nasrudin Abd; Ooi, Boon Teck (Institute of Electrical and Electronics Engineers (IEEE), 2019)
With the increasing demand for electric vehicles, reliability in motor drives is an issue of growing importance. Over the years, various fault-tolerant three-phase motor drive topologies have been introduced and their performances have been investigated. Evaluation of the postfault power of a fault-tolerant drive should take into account both the postfault torque and speed, which depend on both the postfault current and voltage limits. Nevertheless, the postfault motor voltage limits are usually omitted from discussion. Furthermore, current limit in induction motor drive is not as direct as that in permanent magnet motor drive, due to the presence of the flux current. In this paper, the performances of available fault-tolerant three-phase induction motor drives have been reinvestigated, taking into account the impact of not just currents, but also voltage limits for both the inverter and machine. By deriving the postfault machine voltage equations, the effects of machine parameters and operating point on the voltage limit and hence the speed limit are explained. Depending on the topology, the motor may be able to run above the rated speed to gain extra power. The analysis is verified through experiment results on a 1 kW induction machine for four different fault-tolerant drive topologies.